Georgia & the Carolinas - Balfour, Amy C.; Bremner, Jade; Harrell, Ashley; Morgan, MaSovaida; Raub, Kevin; St. Louis, Regis; Ward, Greg (Carlton : Lonely Planet, 2022)
Lonely Planet's Georgia & the Carolinas is our most comprehensive guide that covers all the region has to offer, with recommendations for both popular and lesser-known experiences. Take a trip around Atlanta's Center for Civil & Human Rights and hike in the stunning Great Smoky Mountains National Park - all with your trusted travel companion.
Keywords: History; North Carolina -- Guidebooks; South Carolina -- Guidebooks; Georgia -- Guidebooks